A preliminary description of South African Sign Language syntax - Wright, Donovan (My University, 2017)
This study is a preliminary investigation into the syntax of South African Sign Language. Utilising narrative data within a case study approach, signing is observed and analysed in terms of Radical Construction Grammar. An emphasis is placed on signs as form-meaning pairings, in which information of form is drawn from previous research on the phonology and morpho-syntax of signed languages. Meaning is explained within the same sphere, drawing on established literature regarding meaning in signed languages – with the addition of Mental Space and Conceptual Blending theories. The aim is to describe the signing elicited as in-depth as possible while covering a broad number of relevant aspects. The efficacy of Radical Construction Grammar as a theoretical framework in signed language is also considered. Results include descriptions of different construction types and a holistic view of signing. Schemas are proposed for common constructions, and Radical Construction Grammar is posited as a viable alternative to a traditional understanding of syntax.
A dissertation submitted in fulfillment of the requirements for the Degree of Master of Arts to the Faculty of Humanities, School of Literature, Language and Media, University of the Witwatersrand, Johannesburg, 2017
Keywords: Sign language-Syntax; South African Sign Language